The effect of exercises and insoles on the feet in leprosy patients - Carolina Ribeiro do Prado; Leonardo Cesar Carvalho; Eliane Oliveira Guarda; Christiane Borges Abrão Santos; Wendel Antônio Fagundes; Denise Hollanda Iunes (Universidade de São Paulo, 2019)
ABSTRACT The purpose of this study is to analyze the effects of using customized insoles and leg and foot exercises on the feet of patients with neuropathy caused by leprosy. Thirty volunteers diagnosed with leprosy were assigned to one of three groups: (1) Exercise group (n=10): performed exercises for the intrinsic muscles of the foot; (2) Insole group (n=10): used insoles to correct foot positioning; (3) Insole and Exercise group (n=10): used insoles and performed an exercise routine. The results of the treatments were analyzed with photogrammetry using the Alcimagem® and AutoCAD® programs. Left hindfoot posture changed after treatment in the Exercise and Insole groups (hindfoot, pre versus post <0.001). We also found that combining exercise and insoles did not alter the alignment of the feet during the study's evaluation period (customized insoles and exercises, pre versus post <0.05), which suggests that follow-up for more than four months may be needed. The left hindfoot's alignment can be changed with supervised exercises and the use of insoles.